Approaches to assessment and hazard identification of dioxins - V. Gogol, Elina; I. Gumerova, Guzel; S. Egrova, Olga (International Conference “Environmental Engineering”, 2017)
In the Russian practice in the framework of environmental regulation sanitary measurements to assess the toxicity of the objects of the environment, which are based on the determination of standardized components concentrations and comparing them with the limit value, are widely used. But this approach doesn’t allow assessing the degree of biological hazards for organisms. The biotesting method has been considered for assessing the safety of dioxin-like compounds. Dioxins can be formed out of control in the environment. Ultraviolet radiation accelerates the formation of dioxins, as it enhances the ability of a chemical reaction of chlorine. This phenomenon is well known in Russia, where the chlorination is a standard procedure of water treatment and disinfection of drinking water, and control of the content of chlorophenols is an optional procedure. Simulation of the formation of dioxins in the process of chlorination of water, containing phenolic compounds, was carried out. Process of dioxins transformation in living systems to more toxic metabolites has been described. Enzymes that are involved in detoxification of dioxins have been identified. According to the results of bioassay danger of water samples, containing dioxins, is underestimated, since it doesn’t take into account specific features of metabolism of dioxins in living organisms. Under the action of enzymes in the cells the less toxic compounds can be converted into the more toxic in terms of carcinogenicity and mutagenicity. The system of determination of the dioxin toxic equivalency factor doesn’t account for it. Thus, during determination of danger of xenobiotics in living organisms we should move away from the determination of acute toxicity and focus on the pro cesses that are started by enzyme systems when a toxicant gets into cells of living organisms.
Keywords: dioxins; bioassay; danger to the environment